Kâdî Abdülcebbâr'da İvaz teorisi - Taşer, Berna (My University, 2017)
Muʻtezile, Kâdî Abdülcebbâr, kötülük, elem, bedel, ivaz. ABSTRACT Muʻtazila, Qadi ‘Abd al-Jabbar, evil, pain, the compensation, al- ʿiwaḍ.
Keywords: al- ʿiwaḍ; bedel; Dini yönler; elem; evil; Görüş ve düşünceleri; İslam dini; ivaz; Kâdî Abdülcebbâr; Kelam; kötülük; Muʻtazila; Muʻtezile; pain; Qadi ‘Abd al-Jabbar; the compensation